SOSIALISASI CUCI TANGAN YANG BENAR SEBAGAI UPAYA PREVENTIF PENULARAN COVID-19 DI SD NEGERI 27 PEUSANGAN KABUPATEN BIREUEN PROVINSI ACEH - Irma Fitria; M. Rezeki Muamar; Sri Raudhati; Ferri Zulfahmi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The pandemic due to the prolonged Corona Virus Disease (COVID-19) is engulfing various countries around the world. The epidemiology of COVID-19 has been declared a global pandemic on March 11, 2020 by WHO. The World Health Organization (WHO) issued an appeal regarding the transmission of this virus, one of which is washing hands with soap or what we often hear with the term CTPS (Washing Hands with Soap). Socialization of the correct way of washing hands will be one of the good habits that they will apply and do in their daily lives with the aim of avoiding disease, especially the transmission of the COVID-19 disease which is currently a pandemic. This community service activity was carried out at SD Negeri 27 Peusangan, Bireuen Regency, Aceh Province, totaling 31 students with demonstration methods and audio-visual media. After this service activity, the students were very enthusiastic and became aware of the importance of proper hand washing. It is hoped that this activity will continue to be intensified as one of the efforts to prevent the transmission of COVID-19, especially in Indonesia.